How to prescribe physical exercise in rheumatology - S. Maddali Bongi; A. Del Rosso (PAGEPress Publications, 2011)
Physical exercise, aiming to improve range of movement, muscle strength and physical well being, lately substituted the immobilization previously prescribed in rheumatic diseases. International guidelines, recommendations of Scientific Societies, and structured reviews regard physical exercise as of pivotal importance in treating rheumatoid arthritis, ankylosing spondylitis, osteoarthritis, fibromyalgia syndrome, osteoporosis, and to be considered in connective tissue diseases. Therapeutic exercise should: aim to improve firstly local symptoms and then general health; respect the pain threshold; be a part of a treatment including pharmacological therapies and other rehabilitation techniques, be administered by skilled physiotherapist under the guide of a rheumatologist, be different according to different diseases, disease phases and patient expectations.